Brain Stimulation for Emotion Regulation in Adolescents With Psychiatric Disorders: Study Protocol for a Clinical-Transdiagnostical, Randomized, Triple-Blinded and Sham-Controlled Neurotherapeutic Trial - Konicar, Lilian; Prillinger, Karin; Klöbl, Manfred; Lanzenberger, Rupert; Antal, Andrea; Plener, Paul L. (Frontiers in Psychiatry, 2022)
Background: Anxiety, conduct and depressive disorders represent three highly prevalent psychiatric conditions in adolescents. A shared underpinning of these disorders is a shortcoming in emotion regulation, connected to the functioning of the ventromedial prefrontal cortex. Thus, an intervention able to target the suggested neural correlate seems to be highly desirable, aiming to hinder a maladaptive development of emotion regulation abilities and chronification of associated psychiatric disorders. As transcranial direct current stimulation (tDCS) was repeatedly demonstrated as a safe and noninvasive method to modulate specific brain activity, research is in demand to evaluate neurotherapeutic applications in adolescents with psychiatric disorders. Method: This transdiagnostic, randomized, triple-blind and sham-controlled clinical neurostimulation trial primary aims to investigate if emotion regulation abilities are increased after tDCS in adolescents with psychiatric disorders. Secondly, disorder-specific changes in the anxiety, depression or conduct disorder will be investigated, as well as changes in quality of life, and cognitive and emotional functioning after tDCS intervention. We will include 108 adolescents with psychiatric disorders, displaying a substantial deficit in emotion regulation. Of these, one third each has to be primarily diagnosed with a depressive, anxiety or conduct disorder, respectively. Participants will be randomized to the experimental group (n=54) receiving real anodal tDCS, or to the control group (n=54) receiving sham tDCS. Brain stimulation will be applied for 20 minutes on 5 consecutive days twice targeting the vmPFC. Changes in emotion regulation, together with changes in disorder-specific clinical symptoms will be recorded by multi-informant psychological ratings. To inspect changes in behavior and gaze, computerized tasks and an eye tracker system will be used. Changes in brain responses to emotional and cognitive stimuli will be examined with three fMRI paradigms. In addition, a resting state MRI will be acquired to investigate possible changes in brain connectivity. Discussion: By investigating ‘emotion regulation’ as transdiagnostic treatment target, this project is oriented towards the Research Domain Criteria framework with a dimensional view on mental illness. The study aims at investigating the potential of tDCS as non-invasive intervention for depressive, anxiety and conduct disorders in adolescents and broadening the scientific foundation for its clinical application.